2011
DOI: 10.1177/1079063211409950
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Recidivism Among Adolescents Who Have Sexually Offended

Abstract: The present study investigates the recidivism rates of a sample of 351 male adolescents who sexually offended, and were assessed at an outpatient psychiatric clinic in Montreal, Canada, between 1992 and 2002. The mean age of the participants was 15.8 years (SD=1.8). Data on adolescent and adult recidivism were collected in Summer 2005 from official criminality sources in Canada. Over an 8-year follow-up period, 45% (n=158) of the participants were charged with a new criminal offense, 30% (n=104) were charged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 46 publications
(52 reference statements)
4
42
0
1
Order By: Relevance
“…). The Canadian literature has demonstrated a focus on the causes domain in relation to the secondary level of the public health model of prevention in that authors have shown an interest in the issue of recidivism (Carpentier & Proulx ), as well as in the potential causal relationship between being a victim of sexual abuse and becoming a perpetrator of such abuse (Mallie et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). The Canadian literature has demonstrated a focus on the causes domain in relation to the secondary level of the public health model of prevention in that authors have shown an interest in the issue of recidivism (Carpentier & Proulx ), as well as in the potential causal relationship between being a victim of sexual abuse and becoming a perpetrator of such abuse (Mallie et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible risk factors have not been empirically verified. They include: impulsivity; antisocial personality; high-stress family environments; negative peer associations; and interpersonal aggression (Carpentier & Proulx 2011).…”
Section: Interventions Domainmentioning
confidence: 99%
“…ADHD has also been associated with an earlier onset of antisocial behavior and delinquency (21,59), multiple serious offences (60), higher number of imprisonments and criminal recidivism (21,(61)(62)(63)(64), and more breaches of discipline among incarcerated individuals (21,65). Delinquent behavior among ADHD adolescents is a strong predictor for a high level of caregiver strain (66).…”
Section: Adhd As a Risk Factor For Criminalitymentioning
confidence: 97%
“…Two large meta-analyses of adult and adolescent offenders, respectively, reported a 3.4 and 2.8 times higher prevalence rate of sexualabuse in sex offenders compared to non-sex offenders (Jespersen, Lalumiere, & Seto, 2009;Seto & Lalumiere, 2010). Additionally, sexual victimization in childhood was found to be associated with repeated sexual offending and sexual recidivism in male adolescents (Carpentier & Proulx, 2011;Dennison & Leclerc, 2011) but not in adults (Hanson & Morton-Bourgon, 2005).…”
mentioning
confidence: 89%